Interaksi Sosial Nahdlatul Ulama (Nu) Dan Muhammadiyah Di Desa Sungai Korang Kecamatan Huta Raja Tinggi Kabupaten Padang Lawas - Riska Khoiriah Hasaibun; Irwansyah Irwansyah; Muhammad Jailani (Lembaga Pengembangan Kinerja Dosen, 2024)
The problems examined in this research are related to social interactions between NU and Muhammadiyah in Sungai Korang Village. The two organizations can work together amidst bigotry and differences of opinion. The aim of this research is to determine the factors and forms of social interaction between the NU organization and Muhammadiyah in Sungai Korang village. This research uses a descriptive method with a qualitative research type. The data collection techniques are observation, direct interviews with experts in the field, and documentation. The theory used in this research is Gillin and Gillin's social interaction theory. This theory explains the factors and forms of social interaction in society in the form of activities that create cooperation between people, harmony and harmony in two organizations. The results of this research show that social interaction is influenced by several factors, including: Establishing family relationships, recognition of differences in understanding, high level of meetings, goals to be achieved together, wisdom from the leaders of both organizations who are always good role models. This research also found forms of associative interaction in the form of cooperation in the security sector, mutual cooperation in providing energy, materials and congregations to attend recitations, prioritizing good communication models when organizations make mistakes (accommodation). in any justification where others are invited to participate, or the marriage of different organizations (assimilation). Meanwhile, the dissociative form is competition in the form of words containing envy, and comparing organizations and contraventions can take the form of incitement.